Membangun Budaya Ilmiah: Pelatihan Karya Tulis Ilmiah Bagi Siswa SMAS Buq'atun Mubarakah Pondok Pesantren Darul Aman Gombara, Kota Makassar - Kaslam Kaslam; Angga Anugrah; Ahmad Zulfikar (Sultan Publsiher, 2024)
This community service aims to respond to the increasingly complex challenges in education in the digital era by enhancing the scientific writing skills of high school students in Islamic boarding schools (pondok pesantren). The topic was chosen due to the importance of scientific writing skills in facing global competition and the advancements in information technology. The methodology involved situational analysis to understand the challenges faced by students, designing a structured training program, conducting interactive training sessions, and periodically evaluating the outcomes. The situational analysis revealed challenges such as limited access to literature, low understanding of scientific writing, and lack of motivation among students. The structured training program aimed to address these challenges by providing access to literature, offering intensive guidance in scientific writing, and boosting motivation. Evaluation showed a significant improvement in students' understanding and skills in scientific writing after the training. The active involvement of the Islamic boarding school throughout the service further enhanced the program's overall impact. Consequently, the outcomes of this community service provide a tangible contribution to improving students' academic abilities and supporting the establishment of quality education in Islamic boarding schools. In conclusion, this training program plays a crucial role in enhancing educational quality and preparing students to face future challenges.